Home Security Alarm Using Wemos D1 And HC-SR501 Sensor Based Telegram Notification - Refni Wahyuni; Aditya Rickyta; Uci Rahmalisa; Yuda Irawan (Journal of Robotics and Control (JRC), 2021)
Abstract—Home Security Alarms in today's modern society only use CCTV that can only see the person without any notification that goes into the cellphone in dealing with the theft that occurred. To help the community in dealing with the theft that enters the house, a Home Security Alarm was made using WEMOS D1 and HC-SR501 Sensor with Telegram Notification. The whole tool is divided into several parts which consist of HC-SR501 Sensor, WEMOS D1 and Buzzer. This tool works when the WEMOS D1 microcontroller processes the pear sensor as a motion detector and buzzer as a sound alarm if motion is detected, then the notification automatically enters into the Telegram Application, With this tool can monitor directly if anyone enters the house while being left.